2017
DOI: 10.1177/0013916517702190
|View full text |Cite
|
Sign up to set email alerts
|

Global Social Norms and Environmental Behavior

Abstract: We adopt a recently introduced incentivized method to elicit widely shared beliefs concerning (a) social norms, (b) environmental effect, and (c) difficulty of a wide range of environmental behaviors. We establish that these characteristics, as reflected in elicited beliefs recorded in one sample, predict (out-of-sample) environmental behaviors in a second separate sample. Pro-environmental behaviors perceived to be more socially appropriate and easier to perform, in particular, are more likely to be chosen. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 100 publications
2
29
0
2
Order By: Relevance
“…Since a higher ability to observe internal and external stimuli may also be connected to the salience of social norms, a positive relationship between observing and social norms is plausible. At this point, in further studies, a distinction between descriptive and injunctive social norms or global and local social norms could be valuable in understanding the mechanism (Kormos et al 2015;Vesely and Klöckner 2018). Fourth, an indirect effect of non-judging on goal intention, mediated by attitude, occurred unexpectedly.…”
Section: Relationships Between Mindfulness and Stage-specific Variablesmentioning
confidence: 91%
“…Since a higher ability to observe internal and external stimuli may also be connected to the salience of social norms, a positive relationship between observing and social norms is plausible. At this point, in further studies, a distinction between descriptive and injunctive social norms or global and local social norms could be valuable in understanding the mechanism (Kormos et al 2015;Vesely and Klöckner 2018). Fourth, an indirect effect of non-judging on goal intention, mediated by attitude, occurred unexpectedly.…”
Section: Relationships Between Mindfulness and Stage-specific Variablesmentioning
confidence: 91%
“…Specifically, parents and peers are considered. Second, previous researchers have shown concerns about participants' misperceptions of norms (Borsari & Carey, 2003;Vesely & Klöckner, 2017;Wenzel, 2005), which can affect the research findings. For instance, a person might adjust the perception of norms to his or her own attitudes and behaviors due to the false consensus effect (i.e., people tend to think that others think and act as they do, Mullen & Hu, 1988) or to a need to appear consistent in his or her responses (Cialdini, Trost, & Newsom, 1995;Falk & Zimmermann, 2013).…”
mentioning
confidence: 99%
“…Historical research reported by Gifford [45] suggests the tendency for environmentalists to be middleor upper-class individuals. The 'organic training' variable in this study represented both current societal norms and the transmission of subjective norms [45,47] so that farmers with more organic training not only had received state-sponsored technical training, but also a sense of the current social expectations and patterns of behavior for agricultural producers.…”
Section: Classification Of Farmer Responses By Geographic Categorymentioning
confidence: 99%